Speech accommodation to room acoustics: Reverberation time and clarity - Bottalico, Pasquale; Graetzer, Simone; Hunter, Eric J. (The Journal of the Acoustical Society of America, 2016)
Vocal effort is a physiological entity that accounts for changes in voice production as vocal loading increases, which can be quantified in terms of sound pressure level (SPL). This study investigates how vocal effort is affected by speaking style, room acoustics, and short-term vocal fatigue. Twenty subjects were recorded while reading a text at normal and loud volumes in anechoic, semi-reverberant, and reverberant rooms in the presence of babble noise. The acoustics in each environment were modified by increasing the strength of the early reflections in the talker position. The subjects answered questions addressing their perception of vocal effort, comfort, control, and the clarity of their own voice. SPL variation for each subject was measured per task. It was found that SPL and self-reported effort increased in the loud style and decreased when the reflective panels were present and when reverberation time increased. In contrast, self-reported comfort and control decreased in the loud style, while self-reported clarity increased when panels were present. SPL was higher for females than for males. The lowest magnitude of apparent short-term vocal fatigue was experienced by talkers in the semi-reverberant room. The results indicate that reflections may be used to reduce vocal effort without modifying reverberation time.